PISA – OF STUDENTS AS AN INTERNATIONAL SCIENCE LITERACY ASSESSMENT PROGRAM (Neo Science Peer Reviewed Journal, 2023)
PISA is an international assessment program aimed at assessing the literacy of students in reading (text comprehension), mathematics and natural sciences, and is designed to determine whether students can apply the knowledge and skills acquired at school in real life situations. PISA tests are a step-by-step introduction to these changes . to be able to apply the knowledge students are getting at school in real life, events to analyze, draw the correct conclusions from them and engage in communication. It provides an opportunity to develop skills , participate in international research, and find out about the country's position . In this article, the questions about the use of PISA international assessment programs in education , its importance and possibilities of efficiency are reflected